Pedagogika jako (nie-)gorsza INNA nauka - Śliwerski, Bogusław (Wydawnictwo Naukowe UAM, 2013)
The text analyzes the situation of other science education against the other vs. our own dichotomy. In this perspective, education seen against the background of other humanities and social sciences looks alien to them, especially when poor quality of research leads to the exclusion of pedagogy from the world of science. Pedagogy does not care about its highest academic levels. Despite the fact that education in its part is derived from philosophy, it does not already belong to it like its strange findings in relation to psychology, sociology, ethnography, and political science. The otherness of education is due to a lack of willingness to read pedagogy theses and dissertations by scientists from other disciplines. Moreover it is related with a lack of understanding of the scope and achievements that are evident in terms of methodology and content.
Pedagogy as a (Not-)Worse – OTHER Science
Keywords: education; humanities; social sciences; strangeness; research; psychology; sociology; political science